Marginal donors: can older donor hearts tolerate prolonged cold ischemic storage? - Korkmaz-İçöz, Sevil; Bährle-Szabó, Susanne; Loganathan, Sivakkanan; Li, Shiliang; Karck, Matthias; Szabó, Gábor (Aging clinical and experimental research, 2013)
Both advanced donor age and prolonged ischemic time are significant risk factors for the 1-year mortality. However, its functional consequences have not been fully evaluated in the early-phase after transplantation; even early graft dysfunction is the main determinant of long-term outcome following transplantation. We evaluated in vivo left-ventricular (LV) cardiac and coronary vascular function of old-donor grafts after short and prolonged cold ischemic times in rats 1 h after heart transplantation.
Gesehen am 18.11.2021